THE INFLUENCE OF DISCIPLINE, MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PERUMDA BPR. LAMONGAN REGIONAL BANK - Fika Nur A'isha; Mohammad Yaskun; Noer Rafikah Zulyanti (Sean Institute, 2023)
Thesis entitled “The Influence of Discipline, Motivation and Work Environment on Employee Performance at Perumda BPR. Lamongan Regional Bank” is a study that aims to answer the problems regarding the influence of discipline, motivation and work environment on the performance of paddy employees of Perumda BPR. Lamongan Regional Bank. The research method is quantitative. The sampling technique is simple random sampling with a total of 68 employee respondents. Data collection techniques by observation, interviews and questionnaires. Data processing with the help of SPSS version 20 program. Data analysis using multiple linear regression.